Clinicopathologic Features of Advanced Squamous NSCLC. Issue 9 (September 2016) - Socinski, Mark A.; Obasaju, Coleman; Gandara, David; Hirsch, Fred R.; Bonomi, Philip; Bunn, Paul; Kim, Edward S.; Langer, Corey J.; Natale, Ronald B.; Novello, Silvia; Paz‐Ares, Luis; Pérol, Maurice; et al.
ABSTRACT : N/A: Lung cancer remains the leading cause of cancer‐related death worldwide. NSCLC accounts for more than 85% of all lung cancers, and the prognosis for advanced‐stage disease is typically poor. In recent years, the importance of histologic subtypes of NSCLC has been recognized, and the distinction between squamous and other NSCLC histologic subtypes is now critical to patient management. Squamous cell lung cancer (sqCLC) represents approximately 25% to 30% of NSCLC. The prognosis for patients with advanced NSCLC is poorer for those with sqCLC than for those with adenocarcinoma. This is partly due to a number of clinical characteristics that distinguish sqCLC from other NSCLC histologic subtypes, such as smoking history, comorbid diseases, age, and molecular profile. Together, these factors make sqCLC an especially challenging disease to manage. Herein, we review some of the key clinicopathologic features of sqCLC. Understanding these features to optimally address many of the unique therapeutic challenges of this disease is likely to be central to ultimately improving outcomes for patients with squamous NSCLC.